Forecasting Methane Emission Reduction through 3R Waste Treatment Facility: The Case of Janti-Sidoarjo - Rifai, Muhamad Khafid; Kartikaningsih, Hartati; Susilo, Agus; Kristama, Yoga Sita (Universitas Diponegoro, 2025)
Municipal solid waste (MSW) generation contributes to methane emission, formed during anaerobic decomposition of organic. The MSW reduction can be forced into an integrated solid waste management site through 3R paradigm built in each municipal level area. This is because methane has a relatively short atmospheric lifetime of about 12 years compared to CO2. This means that reducing methane can quickly impact slowing global warming in the short term. This study aimed to achieve maximum results in reduction methane emission generated from an urban area through 3R waste treatment facility with measurable evaluation in 3 scenarios. The method used to gather the data analysis is Minitab 22 software, which forecasts an approach through trend method analysis, moving average, single exponential smoothing, and double exponential smoothing model to obtain the best-fit model for scenario analysis. The result showed that trend analysis has a high accuracy category with the smallest error (<10%: strong accuracy) in BaU, scenario 1, scenario 2, and scenario 3 with the MAPE value 0.002071 (0.2%), MAD value 0.00, and MSD value 0.00. Meanwhile, scenario 3 could decrease the amount of waste sent to landfills 188.03 tons/year in 2024 and 203.53 tons/year in 2033. Whilst, it could reduce methane up to 0.829126 tons-CO2-eq /year in 2024 and 0.897479 tons-CO2-eq /year in 2033 from total waste in Janti or 8-10% from the total methane emissions in Jabon landfill (65683,8 tons-CO2-eq /year). It concluded that optimizing the activities of 3R waste management facility units in each area, particularly in Sidoarjo, can significantly reduce the effect of methane emissions that arise in landfills.